2007
DOI: 10.1002/jts.20223
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and psychological correlates of complicated grief among bereaved adults 2.5–3.5 years after September 11th attacks

Abstract: A Web-based survey of adults who experienced loss during the September 11, 2001, terrorist attacks was conducted to examine the prevalence and correlates of complicated grief (CG) 2.5-3.5 years after the attacks. Forty-three percent of a study group of 704 bereaved adults across the United States screened positive for CG. In multivariate analyses, CG was associated with female gender, loss of a child, death of deceased at the World Trade Center, and live exposure to coverage of the attacks on television. Postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
167
5
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(196 citation statements)
references
References 59 publications
22
167
5
2
Order By: Relevance
“…Second, this study did not include a specific measure of complicated grief. It is likely that in addition to the DSM-IV disorders studied here, some patients developed specific grief reactions associated with post-trauma psychopathology (Neria & Litz, 2004, Neria et al, 2007. Third, because the study was undertaken in an urban general medical practice serving a low-income population, the results may not generalize to primary care settings with different populations (Bruce, Takeuchi, & Leaf, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, this study did not include a specific measure of complicated grief. It is likely that in addition to the DSM-IV disorders studied here, some patients developed specific grief reactions associated with post-trauma psychopathology (Neria & Litz, 2004, Neria et al, 2007. Third, because the study was undertaken in an urban general medical practice serving a low-income population, the results may not generalize to primary care settings with different populations (Bruce, Takeuchi, & Leaf, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…National studies conducted after the 9/11 attacks suggested that between 4% and 11% of the U.S. adult population knew someone who was killed in the attacks of September 11, 2001 (Schlenger et al, 2002;Silver, Holman, Mcintosh, Poulin, & Gil-Rivas, 2002). Although previous reports suggest that unpredictable loss by malicious violence is one of the most psychologically harmful human experiences (Pfefferbaum et al, 2001;Rynearson & McCreery, 1993), only a few investigations have characterized the psychological sequelae of disaster-related loss among those who experienced loss due to the 9/11 attacks (Galea et al, 2002;Neria et al, 2007;Silver et al, 2002).…”
mentioning
confidence: 99%
“…Although most screening instruments showed sufficient psychometric properties there is no evident agreement in the PTSD literature in general and the disaster literature in particular about what is the best screening instrument that can be reliably administered by laypersons in the aftermath of disasters. Similarly, there is a lack of consensus of whether a face-to-face interview is needed for a reliable assessment of postdisaster psychopathology or alternatively whether telephone-based or internet-based (Schlenger et al 2002;Silver et al 2002;Neria et al 2007) surveys are similarly qualified to assess disaster-related PTSD.…”
Section: Classification Of Disastersmentioning
confidence: 99%
“…The sudden death of a loved one through such a human-caused accident can complicate the grief process compared to a loss after an illness (Boelen, de Keijser, & Smid, 2015; Jacobs, Mazure, & Prigerson, 2000; Neria et al, 2007; Prigerson et al, 1997). Furthermore, the sudden loss of a child in an accident is often extremely difficult because children are often closely related to a parent’s sense of self and identity, including how they views themselves in the past, present, and future (Boelen, 2016).…”
Section: Introductionmentioning
confidence: 99%